Design and Analysis of a Single-Band Printed Rectenna Circuit at WiFi Frequency for Microwave Power Transmission - Salih, Ahmad A.; Abdullah, Abdulkareem S. (Iraqi Journal for Electrical and Electronic Engineering, 2019)
In this paper, a single-band printed rectenna of size (45×36) mm 2 has been designed and analyzed to work at WiFi frequency of 2.4 GHz for wireless power transmission. The antenna part of this rectenna has the shape of question mark patch along with an inverted L-shape resonator and printed on FR4 substrate. The rectifier part of this rectenna is also printed on FR4 substrate and consisted of impedance matching network, AC-to-DC conversion circuit and a DC filter. The design and simulation results of this rectenna have been done with the help of CST 2018 and ADS 2017 software packages. The maximum conversion efficiency obtained by this rectenna is found as 57.141% at an input power of 2 dBm and a load of 900 Ω.